Exploiting extracellular polymeric substances (EPS) controlling strategies for performance enhancement of biological wastewater treatments: An overview. (August 2017) - Shi, Yahui; Huang, Jinhui; Zeng, Guangming; Gu, Yanling; Chen, Yaoning; Hu, Yi; Tang, Bi; Zhou, Jianxin; Yang, Ying; Shi, Lixiu
Abstract: Extracellular polymeric substances (EPS) are present both outside of the cells and in the interior of microbial aggregates, and account for a main component in microbial aggregates. EPS can influence the properties and functions of microbial aggregates in biological wastewater treatment systems, and specifically EPS are involved in biofilm formation and stability, sludge behaviors as well as sequencing batch reactors (SBRs) granulation whereas they are also responsible for membrane fouling in membrane bioreactors (MBRs). EPS exhibit dual roles in biological wastewater treatments, and hence the control of available EPS can be expected to lead to changes in microbial aggregate properties, thereby improving system performance. In this review, current updated knowledge with regard to EPS basics including their formation mechanisms, important properties, key component functions as well as sub-fraction differentiation is given. EPS roles in biological wastewater treatments are also briefly summarized. Special emphasis is laid on EPS controlling strategies which would have the great potential in promoting microbial aggregates performance and in alleviating membrane fouling, including limitation strategies (inhibition of quorum sensing (QS) systems, regulation of environmental conditions, enzymatic degradation of key components, energy uncoupling etc.) and elevation strategies (enhancement of QS systems, addition of exogenous agents etc.). Those strategies have been confirmed to be feasible and promising to enhance system performance, and they would be a research niche that deserves further study. Highlights: EPS are of importance for microbial aggregates in biological wastewater treatments. EPS control can cause changes in microbial aggregates and system performance. EPS elevation has great potential in promoting microbial aggregates performance. EPS limitation has great potential in alleviating membrane fouling in MBRs.